Un Pygmalion moderne. L’artiste aux limites de l’art dans "L’OEuvre" d’Émile Zola - Rachwalska von Rejchwald, Jolanta (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2019)
This article introduces a deliberation on the nature and work of an ingenious artist. Frenhofer and Claude Lantier are both artists-painters that try to transcend – thanks to their talents – the limit of their art form. They strive for enriching the otherwise two-dimensional painting plains with the third dimension by “invigorating” women they are creating. In order to do so they are forced to repudiate part of their humanity, to strongly confront reality and to utterly devote all their energy to an idealized concept formed by their imagination. They keep reiterating their work, introducing endless amendments that paradoxically bring about the contrary effect, since the pieces start to be overwhelmed with chaos and disintegration. The question arises whether the created pieces correspond to reality or are they maybe self-portraits of the ingenious artists that lead an inner fight with their internal exemplars?